Optimal Control of the Position of Moisture Transfer Sources in Porous Media (Моделювання, керування та інформаційні технології, 2023)
The paper proposes an approach for finding the optimal position of sources of known power for the quasi-linear Richards equation in a rectangular area. The Kirchhoff transformation is applied with the introduced scaling of coordinates and powers of submerged sources, which allows formulating a dimensionless problem. The task of this study is to find the position of submerged sources - such that the distribution of moisture at the final moment of time is close to the given values or the given target function.